Lower Energy-Demanding Extraction of Bioactive Triterpene Acids by Microwave as the First Step towards Biorefining Residual Olive Skin - Irene Gómez-Cruz; María del Mar Contreras; Inmaculada Romero; Eulogio Castro (Antioxidants, 2024)
In the olive oil industry, a pit fraction is collected from olive pomace and split into a clean pit fraction and a residual olive skin-rich fraction, which does not an industrial application. Therefore, in this work, microwave-assisted extraction (MAE) was applied to obtain high-value triterpene acids (maslinic acid and oleanolic acid) from this biomass using the renewable solvent ethanol. The response surface methodology was used to gain a deeper understanding of how the solvent (ethanol–water, 50–100% v/v), time (4–30 min), and temperature (50–120 °C) affect the extraction performance, as well as the energy required for the process. The effect of milling was also studied and the solid-to-liquid ratio was also evaluated, and overall, a good compromise was found at 10% (w/v) using the raw sample (unmilled biomass). The optimised conditions were applied to residual olive skin sourced from various industries, yielding up to 5.1 g/100 g and 2.2 g/100 g dry biomass for maslinic acid and oleanolic acid, respectively. In conclusion, the residual olive skin is a promising natural source of these triterpene acids, which can be extracted using MAE, releasing extracted solids rich in polymeric carbohydrates and lignin that can be valorised under a holistic biorefinery process.